Strategi Marketing Mix (4P) dalam Memperkuat Citra Merek pada UMKM Hijab: Studi Kasus pada UMKM Bell.Scraft - Cecilia Indah Hapsari; Ery Tri Djatmika; Puji Handayati (Jurnal Manajemen Riset Inovasi, 2026)
This study is motivated by the increasing competition in the Muslim fashion industry, which encourages SMEs to develop effective marketing strategies to build brand image. The purpose of this study is to analyze the implementation of the marketing mix (4P) strategy in strengthening the brand image of Bell.Scraft SMEs. This research employs a qualitative approach using a case study design. Data were collected through interviews, observations, and documentation, and then analyzed using the data analysis techniques of Miles, Huberman, and Saldana, which include data condensation, data display, and conclusion drawing. The results indicate that the product aspect is carried out through continuous trend research and market needs analysis, the pricing aspect applies a combination of cost-based and value-based approaches, the distribution aspect utilizes a multichannel strategy through resellers, social media, and marketplaces, while the promotion aspect focuses on trust-based digital strategies through authentic content and influencers. Overall, the implementation of the marketing mix (4P) supports the strengthening of Bell.Scraft’s brand image amid market competition. The implications of this study suggest that the use of integrated and digital-based marketing strategies can enhance the competitiveness of SMEs and build long-term relationships with consumers.